Enhancement of fingerprint image using wiener filter - Devi, R.; Sujatha, P. (International Journal of Engineering and Technology, 2017)
A fingerprint is one of the most vital Biometric traits used for Personal Identification. To identify and match the fingerprint accurately, it has to be enhanced efficiently. In this paper, an efficient fingerprint enhancement technique is adopted and compared with the existing methods. The proposed methodology consists of three Phases. In the first phase, the fingerprint is subjected to the de-noising process. After adding noise such as salt and pepper, Gaussian and speckle noise, the image is blurred. In the second phase, the fingerprint is filtered with Wiener filter and then de-blurred. In the third, the filtered image is further enhanced for more clarity. The paper emphasizes, the fingerprint preprocessing followed with the enhancement produces better quality image. The performance of the proposed methodology is compared and evaluated using two performances measures namely Peak-Signal-Noise –Ratio and Mean Squared Error using Matlab R2013a.